(untitled) (Studia austriaca, 2018)
In 1918, writing under a pseudonym, Hermann Broch (1886-1951) published a biting critique of the anthropogeographer Erwin Hanslik (1880-1940). This short text, which takes aim at what Broch perceived to be Hanslik’s deterministically reductive and essentialist claims, provides depth and nuance to our current understanding of this early phase of Broch’s critical oeuvre, while also offering more broadly a unique view onto the contemporary debates that played out in the fields of anthropology, cultural studies, history, and philosophy during the first decades of the twentieth century.